2001
DOI: 10.1053/ejvs.2001.1521
|View full text |Cite
|
Sign up to set email alerts
|

Perianeurysmal Fibrosis: a Relative Contra-indication to Endovascular Repair

Abstract: EVAR does not seem to reverse PAF if this is present preoperatively and it induces this condition in approximately one sixth of patients without evidence of preoperative PAF. The potential for this adverse inflammatory local response should be taken into account when considering EVAR for treatment of aneurysms with perianeurysmal fibrosis and must be weighed against the perceived benefits of this approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 13 publications
0
38
0
1
Order By: Relevance
“…Furthermore, it is thought that the development of thrombi in the intrasac functions as a possible trigger of PAI by inducing an autoimmune response. 13 In EVAR cases, physicians often leave thrombi in the intrasac alone, which may not necessarily decrease the inflammatory response. Therefore, although EVAR represents an alternative treatment for IAAAs in patients with appropriate anatomic features, OSR is the preferred therapy in cases involving inflammatory aneurysms complicated by hydronephrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is thought that the development of thrombi in the intrasac functions as a possible trigger of PAI by inducing an autoimmune response. 13 In EVAR cases, physicians often leave thrombi in the intrasac alone, which may not necessarily decrease the inflammatory response. Therefore, although EVAR represents an alternative treatment for IAAAs in patients with appropriate anatomic features, OSR is the preferred therapy in cases involving inflammatory aneurysms complicated by hydronephrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Seven patients (78%) were classified according to the highest grade of the PAF grading of Vallabhaeni et al 14 Preoperatively, three patients were diagnosed with hydronephrosis, one of whom was also presented with creatinine serum levels >1.4 mg/100 mL. Two patients had previously undergone attempted and unsuccessful traditional AAA repair at other institutions (Table I).…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, some authors have published unfavorable results in terms of PAF progression. 14,27,28 Vallabhaeni et al 14 in 2002 concluded that IAAA presents a relative contraindication for EVAR. Barret et al 27 and Jetty et al 28 also reported PAF progression after EVAR.…”
Section: Discussionmentioning
confidence: 99%
“…2). PAF grading established by Vallabhaeni (14) was downgraded from grade 5 to grade 3 overall. PAF enhancement was measured in HU in an effort to reflect the extent of inflammation.…”
Section: Discussionmentioning
confidence: 99%